URBAN PLANNING ORGANIZATION AND DEVELOPMENT OF CHILDREN’S MEDICAL INSTITUTIONS IN UKRAINE - Bulakh, Irina (Journal of Regional and City Planning, 2020)
The urban planning organization and development of children?s medical institutions in Ukraine are considered in this article based on an analysis of the current state of its largest cities, metropolises. Existing problems are outlined, which are primarily related to the excessive number and specialization of medical facilities (compared to European indicators), duplication within the same territory and physical obsolescence of buildings and equipment for medical purposes. This paper contributes to reviewing the transition of planning approaches as well as proposing a fresh approach to the forming of an urban layout of children?s healthcare institutions that is designed to replace the traditional territorial-administrative approach.Abstrak. Artikel ini meninjau lembaga perencanaan kota dan pengembangan institusi medis anak-anak di Ukraina dengan fokus pada analisis kondisi eksisting di kota-kota terbesar, metropolis. Masalah yang ada diuraikan, terutama terkait dengan jumlah yang berlebihan dan spesialisasi fasilitas medis (dibandingkan dengan indikator Eropa), duplikasi dalam wilayah yang sama, keusangan fisik bangunan dan peralatan medis. Makalah ini berkontribusi untuk meninjau transisi pendekatan perencanaan serta mengusulkan pendekatan baru untuk pembentukan tata ruang perkotaan dari institusi kesehatan anak-anak, yang dirancang untuk menggantikan pendekatan tradisional teritorial-administratif.Kata kunci. sistem perencanaan kota dari institusi perawatan kesehatan; lembaga medis anak-anak; Rumah Sakit; klinik rawat jalan.